FAKTOR KETIDAKBERHASILAN PERMA NO 1 TAHUN 2016 DI PENGADILAN AGAMA GUNUNG SUGIH - Ali, Zezen Zainul Ali; Moelki, Moelki Fahmi Ardliansyah (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2021)
Marriages are carried out with the aim of building a family that is sakinah mawadah and rahmah, but on the way the marriage often causes disputes that can lead to divorce, such as in the Religious Court of of Gunung Sugih which has a high divorce rate. Various attempts have been made to reduce the divorce rate, one of which is integrating mediation in the process of settling cases in court. Even so, the implementation of the mediation has not been able to meet the expected objectives because there are still many unsuccessful numbers of mediation at the Religious Court of Gunung Sugih. This research aims to determine the factors that cause the mediation process to be unsuccessful in divorce cases in particular. This research is an empirical legal research or socio-legal research. This research method used in data collection is interviews and documentation then processed and analyzed using descriptive qualitative methods. This research is expected to provide benefits and add scientific knowledge for mediators and researchers to continue working to optimize mediation as an effort to reduce the divorce rate.